Gentrification-induced displacement: a phenomenological study of inner-city residents' experiences in Johannesburg - Ah Goo, Delia Felecia Stephanie (My University, 2018)
With the evolution and the intensification of gentrification, its once clear-cut ties to displacement have been obscured. Displacement is now often denied and contested in the literature and a number of recent studies have provided quantitative evidence of the limited extent of the phenomenon. Questions have also been raised as to whether low-income residents are in fact displaced and whether gentrification is detrimental to the poor. However, the perspectives of people who have been displaced as a result of gentrification have largely been overlooked in the literature, in part due to the methodological difficulty of tracing displaced people. The aim of this study was to explore and to describe the phenomenon of displacement, from the perspective of individuals who lived and/or worked in a gentrifying area in the inner city of Johannesburg, as well as those who had been excluded or physically displaced by gentrification processes. In response to the call for more qualitative approaches to gentrification, a phenomenological approach was used in order to uncover the experience of displacement. In contrast to research that has highlighted the positive effects of gentrification, displacement was found to be a traumatic experience, which had an impact on the overall well-being of the participants of the study. Poor and marginalised people were rendered homeless, causing a disruption in their everyday life-world. The essence of the phenomenon of displacement was found to be one of great pain and loss, which was still experienced by the participants long after their physical relocation had taken place. As the inner city of Johannesburg transforms, reinvestment policies and strategies should therefore seek to be in the interests of the poor and not only the middle class, particularly since today it is home to people who were once denied the right to live there, due to South Africa’s apartheid policies.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018.
Keywords: Gentrification--South Africa; Urban renewal--South Africa; Social classes--South Africa